Breast Tumor-Derived Exosomal MicroRNA-200b-3p Promotes Specific Organ Metastasis Through Regulating CCL2 Expression in Lung Epithelial Cells - Gu, Pengfei; Sun, Mayu; Li, Lei; Yang, Yang; Jiang, Zheshun; Ge, Yang; Wang, Wenbo; Mu, Wei; Wang, Hui (Frontiers in Cell and Developmental Biology, 2021)
Malignant metastasis is the most important cause of death in breast cancer patients, while the lung is a major inflammation and metastatic target organ. Exosomes are nano-sized vesicles that could be uptaken by resident cells to generate the pre-metastatic niche before tumor cells preferentially motility. C-C motif chemokine ligand 2 (CCL2) provided recruitment of immune cells under carcinomas conditions and inflammatory responses. In the present study, we found high expression of CCL2 could recruit the myeloid-derived suppressor cells (MDSCs) and promote lung metastases. Importantly, we established the novel mice model for specific over-expressing CCL2 in the lung, to verify the organotropic metastasis was not because of the enhanced tumor cell proliferation, but the regulatory expression of CCL2 in the target organ. Furthermore, CCL2 expression in the lung was regulated by BC-derived exosomes. During these processes, exosomes play essential roles in the reprogramming of alveolar epithelial type II cells through stimulating various cytokines and mediators. The exosomal microRNA-200b-3p directly binds to PTEN, which involving in AKT/NF-κBp65/CCL2 signaling cascades.